Negara Hukum dan Hak Asasi Manusia di Indonesia - Jamilah, Jamilah; Listiani, Meri; Adhaini, Dina; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The concept of the State of Law is a universal concept that is embraced by almost all countries in the world. In general, the type of state of law is divided into two, namely the state of law of the Rechtsstaat and the state of law The Rule of Law. Both types of legal states have their own characteristics, but they have similarities, namely related to the protection of human rights. This article will discuss the Indonesian Rule of Law from the perspective of the Rechtsstaat and The Rule of Law type and discuss the concept of Human Rights in Indonesia. This article is a normative legal research with a legislative approach, conceptual regulation and historical approach. The results of the study show that the State of Indonesia qualifies as a state of law based on indicators of the Rechtstaat and The Rule of Law types. Meanwhile, related to the concept of Human Rights based on the Indonesian Rule of Law, there is a balance between the rights and obligations of citizens and the Government based on the concept of mutual cooperation and the principle of harmony. This is what is the characteristic of the Indonesian State of Law or also called the State of Pancasila Law.